Physico-chemical and microbiological characterization of the “saburá” from Jandaíra bee (Melipona subnitida) (Research, Society and Development, 2022)
The fermented pollen from stingless bees (saburá) has been gaining prominence in brazilian national market due to its nutritional value, medicinal properties and unique flavor. However, the physicochemical and microbiological characteristics of this product remain unknown, since each species of stingless bee produces a different variety of saburá and there are a few studies carried out about it. The objective of this work was to determine the physicochemical and microbiological characteristics of the Jandaíra bee saburá (Melipona subnitida) from the semiarid region of the state of Rio Grande do Norte. Six samples of jandaíra bee saburá were collected in meliponaries in rural and urban areas of Mossoró city, Brazil. Microbiological analyzes of total mesophilic bacteria, total coliforms and Escherichia coli, Staphylococcus sp., Salmonella spp., molds and yeasts and lactic acid bacteria were performed. In addition, the samples were submitted to physical-chemical analysis of dry matter, mineral matter (ash), crude protein, ether extract, total sugars and neutral detergent fibers (fibers), pH and acidity of the samples. There was no detection of microorganisms in the analyzed samples. This could be an indication that the biochemical and microbial processes managed by bees are efficient in inhibiting the deterioration of this product. As for the physical-chemical parameters, the saburá analyzed presented average moisture contents of 27.2 g/100 g; crude protein 31.1 g/100 g; total sugars 55.2 g/100 g; pH 3.5 and acidity 1023.7 mEq/kg. Thus, the jandaíra bee saburá proved to be a food rich in proteins and carbohydrates and safe for human consumption.